(untitled) (International Journal of Geoscience, Engineering and Technology, 2022)
As the technological development at present it is possible to observe the use of technological tools applied in teaching for object-learning, these are tools that allow the student-teacher integration in a playful and objective way, being able to deal with several subjects in the present work, we sought to if the applicability of a virtual board game as a learning object with the objective of implementing questions, curiosities and information on the theme of dams and, at the same time, taking the format of traditional games, being able to have direct applicability in schools and universities with didactic alternative of teaching through the online platform Flippity, which makes it possible to easily and quickly modify the content present in the games, as it uses simple programming logic through google spreadsheet.